An iterative approach for the determination of tailored blanks for waste-free composite forming by means of FE forming simulation. (2017) - Dörr, Dominik; Lipowsky, Lukas; Schirmaier, Fabian J.; Kärger, Luise; Henning, Frank
Forming of composite pre-products into complexly shaped geometries is one of the most determining process steps in the manufacturing of continuously fibre-reinforced composites. An educated guess of the tailoring of the pre-product (tailored blank), which leads to the desired contour after forming, is in the most cases not possible. An iterative and a direct approach, which facilitate the determination of a tailored blank, based on finite element forming simulation, are presented. Both approaches are successfully applied to a box-shaped, generic geometry and thermoplastic UD-tapes, as well as to a light pod of an automotive boot-lid and a woven engineering textile. It is shown, that the iterative approach is necessary for a reliable determination of a tailored blank, if there is an influence of the areas outside the desired contour for the non-tailored blanks.